Proceedings of the Aristotelian Society / New series - Vol. LXXXI - Aristotelian Society (Great Britain) (London, The Aristotelian Society, 1981)
The proceedings of the Aristotelian Society contains the papers read at the Society's fortnightly meetings in London throughout the academic year
Imprint varies
Mode of access: World Wide Web
Keywords: Philosophy -- Periodicals; Electronic journals; Periodicals; Periodicals; Conference papers and proceedings